Recovery of iron compounds and cobalt solutions from mining tailings - Zamarreño-Bastías, Ricardo; Mera, Adriana C. (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This work present a low-cost, non-traditional and environmentally sustainable process for the recovery of iron and cobalt from mining tailings is presented. The iron is recovered with a 20% hydrochloric acid leaching, recovering the iron as ferric chloride in solution or solid ferric hydroxide, both compounds widely used in industry. Cobalt is extracted with a solution formed by tartaric acid and hydrogen peroxide, extracting an average of 97.66% at the pre-metallurgical laboratory level and with zero order kinetics.